Calculating Distances Between Wireless Nodes for Wireless Network Localization - Martin-Escalona, Israel; Barcelo-Arroyo, Francisco; Ciurana-Adell, Marc (Recent Patents on Telecommunication, 2012)
This paper presents a patent targeted to obtain distance measurements between nodes belonging to a wireless network. The main motivation for this patent is the measurement of the distance between a user device and an access point (or base station). After several distance measurements to different access points at sight and assuming the position of the access points known, the device can compute its own position by trilateration. The main advantage in front of previously existing methods to obtain distance measurements is that the method presented here involves only software modifications to legacy terminals, thus allowing avoiding the need for hardware modifications at the user terminal.
Keywords: round trip time